Link and match learning on the quality of vocational graduates in Banten province, Indonesia - Gholibi, Muhammad Ibra; Syadeli, Syadeli; Suherman, Suherman; Anriani, Nurul; Worapun, Wittaya (Journal of Green Learning, 2024)
Many vocational graduates have not been absorbed in the world of work. The low outcome of vocational graduates is not absolute because there are no jobs, but it is caused by low graduate competence among them. This study aims to determine the influence of link and match learning on the quality of vocational graduates in Banten Province. This study employs a qualitative methodology and a case study research design. Document studies, interviews, and observations were used to gather research data. The study's findings demonstrate that the idea of a link and match describes how organizations and the workplace interact. In other words, it can be said to be a relationship between labor providers and their users. Through these relationships, educational institutions as labor providers can establish relationships with the business world or industry. Vocational education, in particular, can collaborate with companies or industries so that students can practice (internship) in the company. With this program, vocational can determine the competencies most needed in work and the industrial world. The final result of the link and match program is the acquisition of graduates who are ready to work with qualified skills.